2007
DOI: 10.1007/s10787-007-1549-5
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of VEGF to gastric low grade MALT lymphoma by Helicobacter heilmannii infection in C57/BL/6 mice

Abstract: Hh was shown to be related to the formation of MALT lymphoma and VEGF is suggested to play a role in this lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 8 publications
0
14
1
Order By: Relevance
“…It has already been reported that lymphoma cells migrate into the lamina propria mucosae and ischemia leads to vascular endothelial growth factor (VEGF) activity. Neovascularization induced by VEGF might be related to the TLA feature . Therefore, a target biopsy may contribute to an inaccurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been reported that lymphoma cells migrate into the lamina propria mucosae and ischemia leads to vascular endothelial growth factor (VEGF) activity. Neovascularization induced by VEGF might be related to the TLA feature . Therefore, a target biopsy may contribute to an inaccurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Neovascularization induced by VEGF might be related to the TLA feature. 5,18,19 Therefore, a target biopsy may contribute to an inaccurate diagnosis. Nakamura et al 20 reported the predictive value of endoscopic ultrasonography for regression of gastric MALT lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…This finding could be helpful as superficial depressed-type le- sions potentially include circumscribed atrophic gastritis and poorly-differentiated adenocarcinoma. Nakamura et al [15][16] studied mouse gastric MALT lymphoma and reported that VEGF activity in the gastric MALT lymphoma area can potentially induce angiogenesis, and therefore, a rich vascular system is observed in this area compared with normal areas. Further study is necessary to determine whether VEGF also contributes to the generation of abnormal blood vessels observed in human gastric MALT lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…We have established a mouse model of the gastric MALT lymphoma by per oral infection of H. heilmannii from the cynomolgus monkey . By immunohistochemical analysis of the hypoxia using hypoxyprobe‐1 and HIF1‐α antibody, this tumor clearly shows a hypoxic area and HIF1‐α immunoreactivity with similar localization (Figs ); we, therefore, considered that this model is suitable for the investigation of the altered microcirculation in malignant tumors.…”
Section: Discussionmentioning
confidence: 99%